MOLECULAR GENETIC ANALYSIS OF HEREDITARY OF MORPHOBIOLOGICAL AND ECONOMIC CHARACTERISTICS OF COTTON-PLANT - Komilov Doniyor Jo’raevich; Mirzaolomov Sherzodbek Mirzavalievich (Galaxy International Interdisciplinary Research Journal, 2023)
The paper presents the results of a study on the study of the morphobiological and economically valuable characteristics of cotton using traditional and molecular genetic methods. As the objects of study was chosen F2 generation hybrids, derived from hybridization wild-type of cotton G.hirsutum ssp. purpurascens var. el-salvador with the variety “Kupaysin”.